Identification of essential residues for binding and activation in the human 5-HT7(a) serotonin receptor by molecular modeling and site-directed mutagenesis - Impellizzeri, Agata Antonina Rita; Pappalardo, Matteo; Basile, Livia; Manfra, Ornella; Andressen, Kjetil Wessel; Krobert, Kurt Allen; Messina, Angela; Levy, Finn Olav; Guccione, Salvatore (Frontiers in Behavioral Neuroscience, 2015)
The human 5-HT7 receptor is expressed in both the central nervous system and peripheral tissues and is a potential drug target in behavioral and psychiatric disorders. We examined molecular determinants of ligand binding and G protein activation by the human 5-HT7(a) receptor. The role of several key residues in the 7th transmembrane domain and helix 8 were elucidated combining in silico and experimental mutagenesis. Several single and two double point mutations of the 5-HT7(a) wild type receptor were made (W7.33V, E7.35T, E7.35R, E7.35D, E7.35A, R7.36V, Y7.43A, Y7.43F, Y7.43T, R8.52D, D8.53K; E7.35T-R7.36V, R8.52D-D8.53K), and their effects upon ligand binding were assessed by radioligand binding using a potent agonist (5-CT) and a potent antagonist (SB269970). In addition, the ability of the mutated 5-HT7(a) receptors to activate G protein after 5-HT-stimulation was determined through activation of adenylyl cyclase. In silico investigation on mutated receptors substantiated the predicted importance of TM7 and showed critical roles of residues E7.35, W7.33, R7.36 and Y7.43 in agonist and antagonist binding and conformational changes of receptor structure affecting adenylyl cyclase activation. Experimental data showed that mutants E7.35T and E7.35R were incapable of ligand binding and adenylyl cyclase activation, consistent with a requirement for a negatively charged residue at this position. The mutant R8.52D was unable to activate adenylyl cyclase, despite unaffected ligand binding, consistent with the R8.52 residue playing an important role in the receptor-G protein interface. The mutants Y7.43A and Y7.43T displayed reduced agonist binding and AC agonist potency, not seen in Y7.43F, consistent with a requirement for an aromatic residue at this position. Knowledge of the molecular interactions important in h5-HT7 receptor ligand binding and G protein activation will aid the design of selective h5-HT7 receptor ligands for potential pharmacological use.